Interaction of flavones with DNA in vitro: structure–activity relationships. Issue 42 (10th May 2015) - Tu, Bao; Chen, Zhi-Feng; Liu, Zhi-Juan; Cheng, Li-Yang; Hu, Yan-Jun
<x xml:space="preserve">Abstract</x> The structure–activity relationship of the different flavones has been investigated, which may meaningful for drug discovery, and novel drug design.